Perspektif Guru PAI terkait Pendidikan Inklusi bagi Siswa Berkebutuhan Khusus di SMPN 6 Tuban - Agustin, Fia Ayu Putri; Riyadi, Abdul Kadir; Amrullah, Moh. Adib (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to examine the concept of inclusive education for students with special needs at a junior high school in Tuban, East Java, Indonesia, and to explore the perspectives of Islamic Religious Education (PAI) teachers regarding its implementation. The study employs a qualitative approach with a field research design. Data were collected through interviews and documentation, and analyzed using the Miles and Huberman model, which includes data collection, data reduction, data display, and conclusion drawing. The findings indicate that inclusive education is implemented through a pull-out model, supported by collaborative efforts among school stakeholders. In addition, PAI teachers demonstrate varied perspectives toward inclusive education while actively seeking to understand students with special needs through professional development activities and collaboration with special assistant teachers.